2014
DOI: 10.1021/cm501055k
|View full text |Cite
|
Sign up to set email alerts
|

High Light Yield of Sr8(Si4O12)Cl8:Eu2+ under X-ray Excitation and Its Temperature-Dependent Luminescence Characteristics

Abstract: In this work, we first investigate the relationship between temperature and lattice parameters by means of Rietveld refinement and then demonstrate its impact on the luminescence peak position of Eu2+ in Sr8(Si4O12)­Cl8. It is found that with increases in temperature, lattice expansion takes place without significant distortion of the coordination around Eu2+. As a result, the crystal field splitting of the Eu2+ 5d state decreases. At the same time, with the experimental data of the full width at half-maximum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
86
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(91 citation statements)
references
References 35 publications
5
86
0
Order By: Relevance
“…As temperature increases, the X-ray excited luminescence intensity first decreases between 10 and 50 K, then increases towards 130 K, and reduces steadily at higher temperatures. In all crystals, the FWHM of X-ray excited luminescence peaks increases with increasing temperature, consistent with the spreading of excited electrons to high vibrational levels37.…”
Section: Resultssupporting
confidence: 74%
“…As temperature increases, the X-ray excited luminescence intensity first decreases between 10 and 50 K, then increases towards 130 K, and reduces steadily at higher temperatures. In all crystals, the FWHM of X-ray excited luminescence peaks increases with increasing temperature, consistent with the spreading of excited electrons to high vibrational levels37.…”
Section: Resultssupporting
confidence: 74%
“…The PL spectra of the KMg 4 (PO 4 ) 3 :0.06Eu 2+ phosphor present a 52.2nm full width at half-maximum (FWHM) broad blue emission band extending from 400 to 525nm peaking at 450nm, which is assigned to the 4 f 6 5 d –4 f 7 transition of the Eu 2+ ions. Moreover, The PL of KMg 4 (PO 4 ) 3 :0.06Eu 2+ detected under 365nm is similar to that under 300nm in addition to the difference of the relative intensity, which verifies that the Eu 2+ ions occupy the same lattice site (K + sites) in KMg 4 (PO 4 ) 3 host18. Above result is in accord with the conclusion from Rietveld refinement.…”
Section: Resultssupporting
confidence: 85%
“…The temperature-dependent of emission FWHM is related to the configuration coordinate model and the Boltzmann distribution, and can be expressed by:1829where W 0 is the FWHM at 0°C, hv represents the vibrational phonon energy, S means the Huang−Rhys parameter, and k is the Boltzmann constant. With the temperature increase, the excited electrons spread to higher vibration levels and the radiative transitions from these different levels cause the emission band broadening.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, we also observed that the FWHM of the emission band increases from 54 nm to 75 nm as the temperature increased. The temperature-dependence of emission FWHM is related to the configuration coordinate model and the Boltzmann distribution, and can be expressed by: 88,89 …”
Section: Temperature-dependent Photoluminescence Behaviormentioning
confidence: 99%